Ajuste de tecnología en el manejo integrado de plagas y enfermedades en el cultivo de banano orito (musa sp.) En el Cantón La Maná, Provincia de Cotopaxi. - Herrera Parrales, Katerine Alexandra (2016)
The setting technology management integrated pest and diseases in the cultivation of banana Orito (Musa sp.) was carried out with the objective of define a sustainable model in the cultivation of banana Orito, establishing a diagnosis of the technology used by the producer to fight pests and diseases prevalent in the area of study, thus disseminating knowledge about technologies according to the local producer of conditions Orito. Research was carried out in the Recinto San Antonio Manguila, ubicado en el cantón La Maná, Provincia de Cotopaxi. Divided into stages, the first identified the phytosanitary problems, knowledge of the producer and existing technology; the second stage, was determined the methodology of the work carried out on his plantation; in the third stage the experimentation, is developed a plot demonstration by applying the adjustment of technology. As the results came to the following conclusions: producers have little technology for the cultivation of Orito and which use is adapted from other musaceae such as banana and plantain; the 60% of the units productive are in associate with cocoa, and integrate the breeding of animals; stands out that 70% of farmers has between 5 and 30 years dedicated to the production of Orito. The 90% not receive assistance technical showing limitations with regard to the knowledge of the management of pests, diseases and their damage; major phytosanitary problems in 90% scale insects and trips include 80%. Also have a high degree of conformity and reliance on intermediaries for the marketing of its fruit, which makes them reluctant to both receive and use technical information, however, dictated skills positively increased the knowledge and interest of the producers in the health activities of cultivation highlighting cultural management, and alternatives such as diversification in their crops